Effect of aeration and method of addition of glucose sugar to culture medium on growth and sporulation of some Bacillus thuringiensis isolates from Sudan soils - Ahmed, Abdulwahab; Dirar, Hamid (Gezira Journal of Agricultural Science, 2018)
An experiment was conducted in the microbiology laboratory at the Faculty of Agriculture, University of Khartoum in the year 2003 to study the effect of aeration and method of addition of glucose sugar on growth and sporulation of three selected B. thuringiensis isolates (BR12, N10 and EA3) derived from Sudan soils. The isolates responded differently to air supply. Spore counts of isolate BR12 and EA3 increased with an increase in air supply. The highest count was produced at 19:1 air-to-medium ratio (v/v) and the lowest count at 3:1 ratio, whereas the highest spore count by isolate N10 was produced at 4:1 air-to-medium ratio (v/v) and any increase in aeration levels resulted in lower counts. On the other hand, method of addition of glucose sugar was found to affect both pH pattern during incubation period and spore count in the final culture for all selected isolates. Fed-batch addition of glucose resulted in survival of many growing cells which would have been killed in case of batch addition, with subsequent better sporulation. The effect of method of addition of glucose sugar on growth and sporulation of the tested isolates was found to be significant at 1% level.      أجريت تجربة بمعمل الأحياء  الدقيقة بكلية الزراعة، جامعة الخرطوم، في العام 2003م لدراسة تأثير التهوية ونمط إضافة السكر علي نمو وتجرثم بعض سلالات  البكتيريا من نوع  Bacillus thuringiensis والتي تم  عزلها من الترب السودانية. تم اختيار ثلاث عزلات لهذه الدراسة  هي EA3 ، N10 ، BR12. استجابت العزلات للتهوية بمعدلات مختلفة، حيث وجد أن معدل التجرثم ازداد  بزيادة التهوية للعزلات  BR12  ،  EA3  وأعلي معدل تجرثم للعزلتين حدث عند معدل تهوية 19:1 (هواء : وسط نمو [v/v] ) بينما أقل معدل عند 3:1. أما العزلة N10 فقد كان أعلي معدل تجرثم عند معدل التهوية 4:1 ووجد أن أي زيادة في التهوية أدي إلي نقصان التجرثم. وفي الجانب الآخر فقد وجد أن نمط إضافة السكر إلي وسط النمو يؤثر علي نسق الأس الهيدروجيني بوسط النمو ومعدل التجرثم للعزلات  المختارة. أدي إضافة السكر علي جرعات إلي نجاة الكثير من الخلايا الباكتيرية والتي كانت ستموت في حالة إضافة السكر جرعة واحدة مما حسن معدل التجرثم.   إحصائيا وجد أن هناك فرق معنوي لنمط  إضافة السكر عند احتمال 1% .